Mandailing Scholar of the XX Century: Sufism Thought of Syeikh Syihabuddin Nasution Aek Libung (1892 -- 1967) - ., Erawadi (KnE Social Sciences, 2023)
This article aims to describe the sufismtrought of SyihabuddinAekLibung (Nasution), born in South Tapanuli. He was one of the scholars (al-‘Alim al-‘Allamah) in Archipelago, pupil of Abdul Jabar al-KhalidiNaqsyabandi (Khalifah of Ibrahim al-Khalidi) and Muhammad Ali Ridha in Mecca. This article is based on the sources of his manuscript, Adab al-Muridin and Fath al-Qalb with a philological approach and social history. Syihabuddin said that the pillars of the religion are 4 types: iman, Islam, tauhid, and makrifah. It means that religion was not only iman, Islam (sharia, fiqh), dantauhid, but also makrifat (sufism, tarekat and suluk). The understanding and implementation makrifah, of course, must be preceded by the understanding and implementation of the iman, Islam and tauhid. This understanding is the understanding of the scholars who are rapprochement or reconciliation between shari’ah-oriented scholars and sufis who prefer the esoteric teachings. In the practice of sufism, Syihabuddin affiliated to the Naqsyabandiyah. Keywords: Sufism; tarekat; suluk; social history